2018
DOI: 10.1029/2018tc005110
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Viscoelastic Stress Transfer in Long‐Term Earthquake Cascades: Insights After the Central Italy 2016–2017 Seismic Sequence

Abstract: Central Italy is characterized by a network of active faults that interact in a complex manner.Coseismic Coulomb stress changes have been invoked by several authors to explain the concentration of moderate-to-strong earthquakes in this region, but none has considered the time-dependent viscoelastic relaxation of the lower crust and upper mantle as a possible additional source of stress changes at a regional scale. Here starting from the 1915 M w 6.9 ± 0.2 Fucino earthquake, we calculated the coseismic plus pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 77 publications
0
34
0
Order By: Relevance
“…On the contrary, we estimate that the cumulated moment released the Mount Gorzano fault (April 2009, 24 August 2016, and 18 January 2017), corresponding to a cumulated M w of ~6.1, is still far from the maximum magnitude expected in the literature on the fault (6.6–6.7; Galadini & Galli, ; Pace et al, ). Verdecchia et al () recently suggested a contribution of the coseismic and postseismic viscoelastic stress transfer in controlling the seismic sequence evolution, including the participation of the two major faults.…”
Section: Seismotectonic Modelmentioning
confidence: 99%
“…On the contrary, we estimate that the cumulated moment released the Mount Gorzano fault (April 2009, 24 August 2016, and 18 January 2017), corresponding to a cumulated M w of ~6.1, is still far from the maximum magnitude expected in the literature on the fault (6.6–6.7; Galadini & Galli, ; Pace et al, ). Verdecchia et al () recently suggested a contribution of the coseismic and postseismic viscoelastic stress transfer in controlling the seismic sequence evolution, including the participation of the two major faults.…”
Section: Seismotectonic Modelmentioning
confidence: 99%
“…It is unclear because on the 30 October 2016, before field surveys of the 26 October earthquakes, a M w 6.5 earthquake ruptured the total length of the Mt. Vettore fault, rerupturing locations that slipped in the 24 August 2016 earthquake and perhaps those on the 26 October (see Figures , , and ; Calderoni et al, ; Cheloni et al, ; Chiaraluce et al, ; Civico et al, ; Falcucci et al, ; Ferrario & Livio, ; Lavecchia et al, ; Mildon et al, ; Pavlides et al, ; Perouse et al, ; Pizzi et al, ; Porreca et al, ; Scognamiglio et al, ; Verdecchia et al, ; Villani, Civico, et al, ; Villani, Pucci, et al, ; Walters et al, ). Meter‐scale offset across surface ruptures was measured with near‐field 1‐Hz global navigation satellite system for the 30 October ruptures, revealing that the ruptures formed within 2–4 s and, before peak ground acceleration, supporting the primary tectonic origin of the ruptures (Wilkinson et al, ; Figure ).…”
Section: Geologic Backgroundmentioning
confidence: 99%
“…A series of four additional moderate magnitude earthquakes, all with extensional kinematics, hits the southern termination of the system with moment magnitudes ranging between 5.0 and 5.5 in the Campotosto area (Figure 1). The cascade type evolution of the sequence typically observed along this sector of the Apenninic chain (Chiaraluce et al, 2004; Papadopoulos et al, 2017; Verdecchia et al, 2018; Xu et al, 2017) prevented additional human losses after the AM earthquake, because many people had already abandoned their habitations.…”
Section: Introductionmentioning
confidence: 99%
“…These sequences belong to a unique 150 km long normal fault system composed by individual contiguous and/or sub parallel, 10–30 km long, SW‐dipping fault segments. Their static and dynamic interaction (Cocco et al, 2000; De Natale et al, 2011; Hernandez et al, 2004; Lavecchia et al, 2012; Mildon et al, 2017; Nostro et al, 2005; Pace et al, 2014; Papadopoulos et al, 2017; Pino et al, 1999; Verdecchia et al, 2018) as well as their interference with compressional structures formed during the previous tectonic phase is still debated (Chiaraluce et al, 2005, Chiaraluce et al, 2011; Chiaraluce, Di Stefano, et al, 2017 Scognamiglio et al, 2018; Buttinelli et al, 2018; Bonini et al, 2019).…”
Section: Introductionmentioning
confidence: 99%